2013
DOI: 10.4067/s0718-95162013005000058
|View full text |Cite
|
Sign up to set email alerts
|

The development and suppressive activity of soil microbial communities under compost amendment

Abstract: Soil is a highly complex system in which bacteria play a dominant role. Soil microorganism biodiversity is extremely important for sustaining the nutrient cycles of soil ecosystems. The diversity of soil bacterial and fungal communities can be influenced by agricultural management. The use of amendments, such as the incorporation of compost into the soil, strongly affects soil microbial communities directly or indirectly. The use of compost can be an important tool to control soil-borne pathogens. Certain grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 25 publications
0
31
0
2
Order By: Relevance
“…Scotti et al (2015) proposed compost application to soils under intensive farming systems combined with woody scraps to achieve significant changes in biological parameters. The authors found a rapid and intense boost of enzymatic activities (dehydrogenase, phosphomonoesterase and β-glucosidase) after organic amendments, especially after the second yearly amendment, demonstrating that repeated use of organic amendments should be planned to trigger microbial activity and functionality and improve consequently soil biological fertility.The use of compost can affect soil microbial diversity, as reported byZaccardelli et al (2013a) who showed a clear positive effect on the number of spore-forming bacteria, with an increase directly correlated with the dose of compost. Also in stressed soil, with high saline content, the use of compost can determine an improvement of biological fertility(Lakhdar et al, 2009).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Scotti et al (2015) proposed compost application to soils under intensive farming systems combined with woody scraps to achieve significant changes in biological parameters. The authors found a rapid and intense boost of enzymatic activities (dehydrogenase, phosphomonoesterase and β-glucosidase) after organic amendments, especially after the second yearly amendment, demonstrating that repeated use of organic amendments should be planned to trigger microbial activity and functionality and improve consequently soil biological fertility.The use of compost can affect soil microbial diversity, as reported byZaccardelli et al (2013a) who showed a clear positive effect on the number of spore-forming bacteria, with an increase directly correlated with the dose of compost. Also in stressed soil, with high saline content, the use of compost can determine an improvement of biological fertility(Lakhdar et al, 2009).…”
mentioning
confidence: 69%
“…In this scenario, a recovery of depleted soil organic matter and its maintenance to an adequate level is a critical task. It has been shown that application of organic amendments such as compost is a reliable and effective tool to ameliorate soil structure and both chemical and biological fertility of soils (Ros et al, 2003), as well as to suppress soilborne pathogens (Zaccardelli et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial diversity may have a crucial role in sustaining ecosystem functions and maintaining the natural suppressive activities via compost amendment [30]. Compost microflora were found to be critical in protecting cucumber seedlings from Fusarium oxysporum f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that well-rotten farmyard manure induces the highest increase in microbial counts, potato yield and stem height. Another report, that of Zaccardelli et al [15], investigates the effects of increasing doses of compost on the density of several cultivable soil microbial groups in an agricultural system in Southern Italy. It shows that compost furnishes a high number of spore-forming bacteria exhibiting antibiotic activity against phytopathogenic fungi.…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%